Quantifying wage effects of offshoring: import- versus export-based measures of production fragmentation - Wolszczak-Derlacz, Joanna; Parteka, Aleksandra (Economics and Business Review, 2016)
In this paper we examine the implications of international fragmentation of production on wages in the light of recent methodological developments in offshoring measurement. In particular, we compare the results stemming from two ways of quantifying offshoring – the traditional one based on import statistics and the one obtained from the decomposition of gross exports and input-output information. In the empirical part of our study, we estimate the extended version of wage equation, rooted in the Ricardian model of skills, tasks and technologies where skill specific wages are explained by industry-specific measures of capital, skill supply and offshoring indices. The analysis is performed for a large panel (40 countries, 1995–2011 and 13 manufacturing industries). The results of the FE setting indicate that regardless the way offshoring is measured it is negatively associated with wages. However, when the endogeneity is accounted for, this negative association is sustained only for the export-based measures.